A Feminization of Vulnerability? Female Headship, Poverty, and Vulnerability in Thailand and Vietnam. (July 2015) - Klasen, Stephan; Lechtenfeld, Tobias; Povel, Felix
Summary: This article investigates whether heterogeneous subgroups of female-headed households are worse off than households headed by men. It analyzes the correlates of consumption, shock exposure, and severity, as well as vulnerability to poverty. Using panel data of over 4000 rural households from Thailand and Vietnam, strong evidence of heterogeneity among subgroups of female-headed households are found. In particular, in comparison with male headed households de facto female-headed ones are found to be richer in Thailand, but prone to more severe shocks in both countries. Furthermore, our results suggest that in Thailand single female-headed households are less vulnerable to poverty than households headed by men. However, in Vietnam these households are particularly poor and vulnerable to poverty; we show that this is mostly due to their greater poverty rather than their higher risk exposure. Our findings suggest that differentiation by subgroups of headship is important for policy development and targeting as well as future research.